Vision and Mission of Management Education in Nepal - Koirala, Parashar (Tribhuvan University Journal, 2010)
Not available. Key words: Management education; Industrial and Commercial Sector; Nepal Tribhuvan University Journal Vol. XXV, No. 1, 2005 Page:27-32 Uploaded date: 24, September, 2010